Comparison Between Nylon and Polyglactin Sutures in Pediatric Cataract Surgery: A Randomized Controlled Clinical Trial - Melega, Mathias V.; dos Reis, Roberto; Lira, Rodrigo Pessoa Cavalcanti; de Oliveira, Denise Fornazari; Arieta, Carlos Eduardo Leite; Alves, Monica (Frontiers in Medicine, 2021)
Purpose: To compare the performance of nylon sutures to that of polyglactin sutures in pediatric patients undergoing cataract surgery. Setting: University of Campinas (UNICAMP), Campinas, São Paulo, Brazil Design: A prospective, randomized, partially masked, single-site clinical trial. (https://clinicaltrials.gov/ct2/show/ NCT03812640). Methods: A total of 80 eyes from 80 patients who underwent pediatric cataract surgery were randomized into two groups in block sizes of four. Group A consisted of 41 patients whose surgical incisions were sutured with polyglactin 10-0 material. Group B consisted of 39 patients whose surgical incisions were sutured with nylon 10-0 material. The primary outcome was frequency of suture-related complications in each group. Secondary outcomes were the frequency with which suture removal was necessary. Results: The incidence of suture-related complications within six months of follow up was 0 out of 41 eyes (0.00%) in the polyglactin group and 17 out of 39 eyes (43.59%) in the nylon control group (p<0.001). In all of the eyes with suture-related complications, the sutures were promptly removed. The most frequent complications were vascularization near the suture (17.95%) and loose sutures (17.95%). No ocular or systemic study-related adverse events were observed. Conclusions: Polyglactin sutures were found to be safe and effective for pediatric patients undergoing cataract surgery. Their lower rate of complications and reduced likelihood of removal (and the subsequent need for general anesthesia) make their use preferrable to that of nylon sutures. This study represents the first controlled randomized clinical trial to compare nylon sutures to polyglactin sutures in pediatric patients undergoing cataract surgery. Keywords: pediatric cataract; suture; nylon; polyglactin; suture-related complications